2018
DOI: 10.1080/09513590.2018.1460343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12-month treatment with metformin and/or oral contraceptives on health-related quality of life in polycystic ovary syndrome

Abstract: Health-related quality of life (HRQoL) is impaired in polycystic ovary syndrome (PCOS), but the effect of treatment with metformin (M) and/or oral contraceptives (OCP) is undetermined. To assess changes in HRQoL during 12-month randomized treatment with M, OCP or M + OCP in PCOS. Ninety women with PCOS were randomized to treatment with M, OCP or M + OCP. HRQoL was evaluated by a PCOS-specific visual analog scale (PCOS-VAS) regarding 1: Facial hair, 2: Body hair, 3: Acne, 4: Irregular menses, 5: Weight and 6: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 27 publications
3
29
0
1
Order By: Relevance
“…The carry-over effect was not significant for most outcomes assessed, except for self-image domain at the end of 3 months of therapy (Tables 2-3). [10,26,27], the effect of OCs on psychological health and QOL of PCOS has been investigated only in a limited number of previous studies [11][12][13][14]. Available data showed that treatment with OC was associated with a significant improvement in the QOL in a 16-week randomized controlled trial (RCT) [12], a 12-month RCT [11], and a 6-month observational trial [13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The carry-over effect was not significant for most outcomes assessed, except for self-image domain at the end of 3 months of therapy (Tables 2-3). [10,26,27], the effect of OCs on psychological health and QOL of PCOS has been investigated only in a limited number of previous studies [11][12][13][14]. Available data showed that treatment with OC was associated with a significant improvement in the QOL in a 16-week randomized controlled trial (RCT) [12], a 12-month RCT [11], and a 6-month observational trial [13].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have been suggested that the management of PCOS can improve both physical and psycho-emotional aspects of QOL [9,11,12]. To assess the effects of OCs on QOL domains, we used a specific questionnaire with a multi-dimensional concept, which was developed for examining the impact of PCOS or its treatment on psychosocial-emotional, self-image, fertility, sexual function, hirsutism, and obesity-menstrual disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the recent International Evidencebased Guidelines for the Assessment and Management of PCOS, all women with PCOS should be screened and monitored for QOL status to prevent, identify, and manage their health concerns. While these guidelines recommended that improving the QOL of the patients should consider as an important goal of treatment [11,35,36], the effect of OCs on psychological health and QOL of PCOS has been investigated only in a limited number of previous studies [12][13][14][15]. Available data showed that treatment with OC was associated with a signi cant improvement in the QOL in a 16-week randomized controlled trial (RCT) [13], a 12-month RCT [12], and a 6-month observational trial [14].…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous studies on the association between PCOS and QOL [6][7][8][9][10], a limited number of studies have evaluated the effects of OCs on the QOL of PCOS patients [11][12][13][14]. Besides, to the best our knowledge, there is no study comparing the effectiveness of these pharmacological treatments on the QOL of patients based on their progestin component.…”
Section: Introductionmentioning
confidence: 99%